Dynamic Modelling and Simulation of an Induction Motor with Completely Reduced Stator Transients - Ejiofor, Oti Stephen; Benneth, Nnadi Damian; Uche, Ogbuefi; C.G, Nnabugwu (Journal of Asian Scientific Research, 2019)
Dynamic modelling and simulation of an induction motor is of great significance both in the academic and in the industrial world. The characteristics of an induction motor are represented mathematically. The mathematical representation is modeled with MATLAB/SIMULINK software. The main advantage of this software over other programming soft wares is that, instead of compilation of program code, the simulation model is built up systematically by means of basic function blocks. The dynamic properties of the induction motor are determined from the graphs obtained from the software. A reduced model of the induction motor is modeled by setting the stator transients to zero. In this paper, the complete model and the reduced model are compared. From the results obtained, the reduced model can sufficiently represent the dynamic characteristics of an induction motor - the currents, and rotor speed of the induction motor. Equally, from the results obtained, the torque dynamic characteristics of the motor are however not satisfactorily represented by the reduced model.